Harmonizing business practices of events and convention industry through sustainability assessment framework development - Bart Aswain, Ilanur Elyssa; Ahmad Ludin, Norasikin; Jarimi, Hasila; Purvis-Robert, Kathleen L.; Hamid, Norul Hisham; Mohd Shariff, Mohd Zulkifly; Burke, John (Elsevier, 2024)
The global event and convention industry is singlehandedly one of the largest and most lucrative sectors in business forecasting market size projected at approximately more than two trillion U.S. dollars by 2028. Despite being a significant contributor to global economic growth, the event and convention industry faces a pressing environmental challenge due to its substantial carbon footprint. Current practices in the industry inadequately address sustainability concerns, leading to a critical gap in integrating environmental considerations into core business models. The lack of sustainability considerations contributes to climate degradation and undermines the industry’s long-term success and resilience. This observation signifies the need for a more systematic trajectory toward total decarbonization of the industry through the implementation of sustainable practices across its value chain. This work aims to develop a conceptual framework of sustainability assessment for a case study in the event and convention sector integrating two indicators: greenhouse gas emissions and energy consumption. The result identified a critical gap in current practices regarding the insufficient integration of sustainability assessment into the core financial business models of firms. The authors propose a new approach to address this by integrating economic impact analysis through the employment of the Return of Sustainability Investmentsdiscovered as the most effective sustainability economic impact assessment method in this study. To facilitate optimized implementation, a multilevel strategy framework enabling the adoption of a sustainability assessment is presented in this paper. This paper contributes to improved execution of sustainability assessments, where the framework can be applied in heterogeneous sectors.